Mapping and characterization of a novel powdery mildew resistance locus (PM2) in Cannabis sativa L. - Seifi, Soren; Leckie, Keegan M.; Giles, Ingrid; O’Brien, Taylor; MacKenzie, John O.; Todesco, Marco; Rieseberg, Loren H.; Baute, Gregory J.; Celedon, Jose M. (Frontiers in Plant Science, 2025)
IntroductionBreeding genetic resistance to economically important crop diseases is the most sustainable strategy for disease management and enhancing agricultural and horticultural productivity, particularly where the application of synthetic pesticides is prohibited. Powdery mildew disease, caused by the biotrophic fungal pathogen Golovinomyces ambrosiae, is one of the most prevalent threats to the cannabis and hemp industry worldwide.MethodsIn this study, we used bulked-segregant analysis combined with high-throughput RNA sequencing (BSRSeq) to identify and map a novel single dominant resistance (R) locus (designated PM2), that strongly suppresses powdery mildew infection and sporulation in Cannabis sativa.Results and discussionBSA mapped PM2 to chromosome 9. Histochemical analysis revealed that PM2-induced resistance is mediated by a highly localized hypersensitive response mainly in the epidermal cells of the host. Importantly, genetic markers capable of tracking PM2 resistance in breeding populations were developed using associated SNPs identified in this study. The ability to track PM2 will allow for successful introgression of PM resistance into elite cannabis cultivars and help move towards a more sustainable cannabis industry.